Impact assessment of agricultural research in West Africa: An application of the propensity score matching methodology - Liebenehm, S.; Affognon, Hippolyte D.; Waibel, H. (University of Hannover, 2009)
Ex-post evaluation of agricultural research is aimed to empirically provide evidence of past investments’ effectiveness. This paper is intended to measure the immediate impact of livestock research activities on cattle farmers’ knowledge about trypanosomosis and its curative and preventive control strategies. According to the quasi-experimental design of the intervention, it is shown that its impact will be adequately estimated by propensity score matching (PSM). Based on data collected according to a knowledge, attitude and practice (KAP) questionnaire in the region of Kénédougou that is common to Mali and Burkina Faso, results indicate a significant gain in farmers’ know-how due to participation in livestock research activities.